Carbon Black and Multi-Walled Carbon Nanotube Supported Cobalt for Anion Exchange Membrane Fuel Cell - Truong, Van Men; Yang, Chih-Wei; Yang, Hsiharng (Journal of Technology Innovations in Renewable Energy, 2018)
Carbon black (CB) and multi-wall carbon nanotube (MWCNTs) supported cobalt, namely, CoPc/CB and CoPc/MWCNTs, respectively, with different metal loads was synthesized and used as the cathode catalyst for anion exchange membrane fuel cells. The prepared catalysts were characterized using X-ray diffraction and scanning electron microscopy. The surface morphology analysis revealed heterogeneous cobalt distribution on the carbon support. Cyclic Voltammetry was also studied to investigate the best combination ratio. The results indicated that the electrochemically largest active surface area was observed when 30 and 40 wt% cobalt was combined with 70 wt% CB and 60 wt% MWCNTs, respectively. The anion exchange membrane fuel cell performance showed that both cathode catalysts exhibited the highest peak power density at 40 wt%t. Co load. The peak power density of 55 mW/cm2 at 0.4 volts was obtained using CoPc/CB. Meanwhile, the promising catalyst CoPc/MWCNTs only produced 35mW/cm2, which did not meet the expectation. According to some references, the alkaline fuel cell performance might be bothered by the acid residues, sulfates and nitrates produced by the MWCNT purification process.